(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Pakistan is highly vulnerable to climate change effects despite being a non-contributor to global greenhouse gas emissions1. Extreme temperatures, water insecurities, droughts, landslides, and heat waves have not only left devastating impacts on economy but also compromised physical, social and mental well-being of population. During recent frequent episodes of flooding battered more than two thirds of its districts1. Moreover, it impacts individuals of all ages, with children being particularly vulnerable due to their weaker immune systems and dependence on caregivers2. Pakistan is currently grappling with its most severe flood disaster, which has submerged vast areas, notably in eastern Punjab, followed by Khyber Pakhtunkhwa (KPK), Sindh and Gilgit-Baltistan (GB). Their impact on child health is multifaceted, with immediate public health consequences as well as numerous enduring challenges 2. More than 40% of Pakistan’s population is under 18 years of age (approximately 112 million), child health is a major concern during such catastrophes. UNICEF reported that an estimated 3.4 million children were affected by the 2022 flood tragedy in Pakistan3. The most immediate and evident causes of flood-driven child mortality and morbidity are physical injuries from debris, collapsing structures, drowning, electrocution and snake bites. Furthermore, floods inversely impact child health by increasing the incidence of water-borne diseases such as hepatitis A and E, typhoid, cholera and diarrhea due to widespread water contamination and the breakdown of sewer systems. Stagnant water acts as a breeding ground for mosquitoes, further leads to the spread of vector-borne diseases like malaria and dengue4. Skin problems and respiratory issues also emerge from mold growth in persistently damp environments5.